FURTHER OBSERVATION ON NEWLY LOCATED PRAWN FISHERY OF SAURASHTRA COST - GOPALAN, U K (Fishery Technology, 2025)
The abundance of prawns in a newly located ground off Saurashtra has been described. Catch composition showed that Metapenaeus afinis formed the bulk of the catches. Previously this species was thought to be of not much commercial importance in this region. The peak of the fishery lasted from September to November. Observations on the biology of this species showed that it occurs as an independent stock in this region. The significance of the gear employed in fishing is also emphasized.